2020
DOI: 10.3390/pr8060658
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling and Analysis of the Performance of an Aluminum-Air Battery with Alkaline Electrolyte

Abstract: A numerical model is created to simulate the discharge performance of aluminum-air batteries (AABs) with alkaline electrolyte. The discharge voltage and power density, as a function of the discharge current density, are predicted for the modeled AAB and compared with experimental measurements. A good agreement between model and experiment is found. The effect of various model parameters on the battery performance is studied by adjusting the parameters within a suitable range. The results show that electrolyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Figure 4 f shows that the battery ohmic resistance is greatly reduced from 63 Ω for 74.5 μm electrolyte to 12 Ω for 18.3 μm electrolyte. In the research of Yang et al 39 , 40 , it has also been confirmed that the performance of the battery is affected by the thickness of the electrolyte. As the distance between the two electrodes decreases, the ion diffusion efficiency in the electrolyte increases, the internal resistance of the battery decreases accordingly, and the battery performance improves.…”
Section: Resultsmentioning
confidence: 84%
“…Figure 4 f shows that the battery ohmic resistance is greatly reduced from 63 Ω for 74.5 μm electrolyte to 12 Ω for 18.3 μm electrolyte. In the research of Yang et al 39 , 40 , it has also been confirmed that the performance of the battery is affected by the thickness of the electrolyte. As the distance between the two electrodes decreases, the ion diffusion efficiency in the electrolyte increases, the internal resistance of the battery decreases accordingly, and the battery performance improves.…”
Section: Resultsmentioning
confidence: 84%
“…Owing to higher theoretical capacity (2.98 Ah•g −1 ) and lower cost compared to other metal anode materials, for instance, Mg (2.20 Ah•g −1 ) and Zn (0.82 Ah•g −1 ), the second-highest energy density (8.1 kWh•kg −1 ) after Li (13.3 kWh•kg −1 ), and its low negative electrochemical potential (−1.66 V vs. NHE), aluminum shows great potential for its application in MAB as the negative electrode material. The additional advantages of aluminum include its abundance, rapid mechanical rechargeability, environmental friendliness, and ease of recycling [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%